Determination of Accuracy of Nursing Diagnoses Used by Nursing Students in their Nursing Care Plans - Aydin, Nursel; Akansel, Neriman (My University, 2013)
Aim: The aim of this study was to determine and evaluate appropriateness of nursing diagnoses with NANDA taxonomy used by second year nursing students in their nursing care plans. Methods: Retrospective design. Findings: While care plans included 42 nursing diagnoses appropriate to NANDA II taxonomy, some phrases (n=30)were used as nursing diagnoses. Risks for infection, pain, activity intolerance, anxiety were the most frequently used diagnoses while nursing diagnoses in domains of cognitive-perceptive, self perception and role relations are very few. Conclusio: Performing case studies in clinical settings by using NANDA diagnoses, specifying difficulties experienced by nursing students’ and determining levels of discomfort while assessing the patients and determining the perceptions of nursing students by doing qualitative studies are recommended.
Keywords: NANDA; nursing students; nursing care plans